2015
DOI: 10.1051/0004-6361/201425370
|View full text |Cite
|
Sign up to set email alerts
|

THOR: The H i, OH, Recombination line survey of the Milky Way

Abstract: To study the atomic, molecular, and ionized emission of giant molecular clouds (GMCs) in the Milky Way, we initiated a large program with the Karl G. Jansky Very Large Array (VLA): "THOR: The H , OH, Recombination line survey of the Milky Way". We map the 21 cm H  line, 4 OH lines, up to 19 Hα recombination lines and the continuum from 1 to 2 GHz of a significant fraction of the Milky Way (l = 15• −67• , |b| ≤ 1 • ) at an angular resolution of ∼20 . Starting in 2012, as a pilot study we mapped 4 square degre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 65 publications
(111 reference statements)
9
75
1
Order By: Relevance
“…This is because hydrogen is converted from atomic to molecular (HI-to-H 2 transition) at N(HI) ∼ (9-11) × 10 20 cm −2 for Perseus . However, in general, the uniform HI column density distribution could also result from a large amount of optically thick HI gas (see Bihr et al 2015). The amount of the optically thick HI in Perseus was studied in Lee et al (2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because hydrogen is converted from atomic to molecular (HI-to-H 2 transition) at N(HI) ∼ (9-11) × 10 20 cm −2 for Perseus . However, in general, the uniform HI column density distribution could also result from a large amount of optically thick HI gas (see Bihr et al 2015). The amount of the optically thick HI in Perseus was studied in Lee et al (2015).…”
Section: Resultsmentioning
confidence: 99%
“…In general, HI is an excellent tracer of low column density atomic gas in the far outskirts of molecular clouds. While it can be optically thick closer to giant molecular cloud (GMC) centers (see Bihr et al 2015), HI absorption measurements can be obtained to provide full column density information and to provide insight into the nature of the atomic to molecular transition in GMCs . In particular, we focus our study on the Perseus molecular cloud, whose atomic and molecular gas and dust content, as well as the HI-H 2 transition, has been well studied in a number of previous works (Lee et al 2012Stanimirović et al 2014;Lee et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…H i absorption spectroscopy can in principle be used to overcome this shortcoming. For example, in the framework of the on-going THOR survey (The H i, OH, Recombination line survey of the Milky Way), Bihr et al (2015) calculate the optical depth toward the giant molecular cloud W 43 to estimate the true H i column density. Using Galactic continuum emitters for the H i absorption technique, however, has the intrinsic issue that only the fraction of H i gas in front of the continuum emitter can be accounted for.…”
Section: N Hi Mapmentioning
confidence: 99%
“…• ) during the 2012A semester (Project 12A-161, see also Bihr et al 2015). We used a hexagonal geometry for the mosaic for this 2…”
Section: Vla Observationsmentioning
confidence: 99%
“…Starting in 2012 with a pilot study around the giant molecular cloud (GMC) associated with the W43 star formation complex (Bihr et al 2015;Walsh et al 2016), we observed a large fraction of the Galactic plane in the first quadrant of the Milky Way (l = 14−65…”
Section: Introductionmentioning
confidence: 99%